Yahweh before Israel: glimpses of history in a divine name - Fleming, Daniel E. (Cambridge University Press, 2021)
"Yahweh is the proper name of the biblical God. His early character is central to understanding the foundations of Jewish, Christian, and Islamic monotheism. As a deity, the name appears only in connection with the peoples of the Hebrew Bible, but long before Israel, the name is found in an Egyptian list as one group in the land of tent-dwellers, the Shasu. This is the starting-point for Daniel Fleming's sharply new approach to the God Yahweh. In his analysis, the Bible's "people of Yahweh" serve as a clue to how one of the Bronze Age herding peoples of the inland Levant gave its name to a deity, initially outside of any relationship to Israel. For 150 years, the dominant paradigm for Yahweh's origin has envisioned borrowing from peoples of the desert south of Israel. Fleming argues in contrast that Yahweh was not taken from outsiders. Rather, this divine name is evidence for the diverse background of Israel itself"--